2017
DOI: 10.3389/fpsyg.2017.00695
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Individualism and Their Ramification in Japan: Rising Individualism and Conflicts with Persisting Collectivism

Abstract: Many studies have shown that American culture has become more individualistic over time. However, it was unclear whether other cultures, especially East Asian cultures, have also shifted toward greater individualism. Therefore, this article reviewed studies investigating temporal changes in individualism in Japan and their ramifications on psychology and behavior. Japan has experienced rapid and dramatic economic growth and urbanization and has adopted more social systems based on individualistic concepts in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 65 publications
3
78
0
1
Order By: Relevance
“…Recently, it has been suggested that Japanese culture has become more individualistic and the coexistence of individualism and traditional collectivism would be related to undesirable interpersonal relationships ( Ogihara, 2017 ; Takano and Osaka, 2018 ). The leadership style of listening humbly to each person’s perspectives, empowering them, and trying to empathize with other people would therefore become more important in this culture.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that Japanese culture has become more individualistic and the coexistence of individualism and traditional collectivism would be related to undesirable interpersonal relationships ( Ogihara, 2017 ; Takano and Osaka, 2018 ). The leadership style of listening humbly to each person’s perspectives, empowering them, and trying to empathize with other people would therefore become more important in this culture.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research illustrates that although central cultural norms are still collectivist in Japan, Japan is getting more individualistic (Ogihara, 2017). However, recent research illustrates that although central cultural norms are still collectivist in Japan, Japan is getting more individualistic (Ogihara, 2017).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Germany represents a rather individualistic country (score 67), whereas Japan characterizes a mid-range collectivistic country (score 46). Although Japan does not represent an extreme collectivistic country based on this dimension (and becomes more individualistic, Ogihara, 2017), there is a wide range of research showing the persistence of collectivism in Japan, especially the importance of collectivistic living (increased importance in social obligation, social harmony, and social contribution and decreased importance in individual rights; e.g., Hamamura, 2012;Kito, Yuki, & Thomson, 2017;Ogihara, 2017), and low levels of relational mobility (e.g., Thomson et al, 2018).…”
Section: The Present Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…123], поэтому, вероятно, в исследовании они в меньшей степени обозначили индивидуальные экономические потребности по сравнению с российскими студентами. Полученный результат согласуется с данными других авторов, отмечающих, что, несмотря на увеличение уровня индивидуализма среди японцев, у них сохраняется доминирование установок коллективизма [28].…”
Section: таблица 4 -результаты сравнительного анализа экономических аunclassified